Optimalisasi Wakaf Produktif dalam Pengembangan Ekonomi Mikro Islam - Fadlan Khairi; Lisa Saputri; Astra Adianto Tinambunan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative method by analyzing 15 relevant journals to examine the optimization of productive waqf in the development of Islamic microeconomics. Productive waqf has great potential as an instrument for empowering the people's economy, especially in supporting the sharia-based micro and small business sector. This study found that the use of waqf productively can create economic sustainability through the management of waqf assets for productive activities such as agriculture, trade, and microfinance services. Through good governance strategies, transparency, and adequate regulatory support, productive waqf has been proven to increase community income, create jobs, and reduce economic inequality. In addition, collaboration between professional nadzir and Islamic financial institutions is the key to success in implementing productive waqf. The main obstacles faced include low waqf literacy in the community and limited innovation in managing waqf assets. Therefore, synergy is needed between the government, Islamic financial institutions, and the community to encourage the maximum use of productive waqf in supporting an inclusive and sustainable Islamic microeconomics.